'LITERACIES' – 60+ YEARS OF 'READING' THE AEGEAN LATE BRONZE AGE1. (December 2014) - BENNET, JOHN
<x xml:space="preserve">Abstract</x> Inaugurated in January 1954, the 'Minoan Linear B Seminar' explored the information emerging from Ventris' decipherment of Linear B in 1952. The new academic discipline of 'Mycenaean Studies' rapidly moved on from questions influenced by the field's 'pre‐history' dating back a further 60 years to Evans' first publication on Aegean scripts. Intense philological and epigraphical research in the 1950s and 1960s laid the foundations for comparative study of the Mycenaean palatial societies, while a greater appreciation of archaeological data and contexts moved interpretation on in the 1980s and 1990s. Building on this tradition, Mycenaean studies currently needs more documents to sustain a 'critical mass' of researchers and, ideally, a new Ventris to unlock the Aegean scripts that remain undeciphered.